Study of Ecobiological Characteristics of Spiny Eel (Mastacembelidae) in Elo River, Magelang, Central Java - Maharsi, Ganesh Jatu; Waluyo, Waluyo; Armando, Eric (JFMR (Journal of Fisheries and Marine Research), 2024)
Spiny Eel (Mastacembelidae family) is a freshwater fish that lives in various types of waters. Spiny eel is a potential fish that is still very rarely researched and developed. Continuous fishing has resulted decreasing number on spiny eel in the nature. This study aims to find out how the ecological and biological aspect of spiny eel in the Elo River, Magelang City, Central Java. This study used a random sampling method with minimum sample of 30 spiny eel from the wild. Data collection techniques were carried out by direct observation and by conducting a review of previous research literatures. The research results showed that the habitat of the spiny eel in the Elo River was suitable for the spiny eel to live in. There were three types of spiny eel obtained, namely Macrognathus circumcinctus, Macrognatus maculatus dan Mastacembelus unicolor with a total number of 36. Spiny eel has a negative allometric length growth pattern. The sex ratio of the spiny eel is 1.4:1. The majority of gonadal maturity level are in second stage. The average of GSI (gonadosomatic index) of male and female were 0.727% and 1.621%. Fecundity of female fish ranged from 2614 – 46233 eggs. Theoritical age is divided into three, Macrognathus circumcinctus, Macrognatus maculatus dan Mastacembelus unicolor have the average of 3.8, 7.27 and 4.67 months. Spiny eel really loved worms and crustaceans (crab and shrimp / prawn) as their main feed (IP 38.83%) and (IP 39.67%) then shrimp / prawn as their complementary feed (IP 14,63%) aquatic microinvertebratae for their additional feed (IP 4.73%) and left with unidentified feed (IP 1.15%).